Reviewing China’s Unequal Education System Based on Ecological System Theory - Wang, Xining; McGuckin, Conor; Zhang, Chengming (Universitas Negeri Malang, 2023)
This review examines China’s educational system the “two-track system” and rural education challenges through the lens of Bronfenbrenner's Ecology System Theory. Using a theoretical framework to review related literature can support readers in understanding the intricate interplay between societal factors, cultural influences, policy decisions, and specific issues. Therefore, this aims to understand how the ecological environment shapes rural education’s development until today, and the Ecological System Theory is used as a theoretical guidance. To find the potential answer to proposed research questions (RQ): RQ 1. What is the background of rural China and the